Evaluación del efecto del macerado a base de chocho seco y tierno para el control de plagas en el cultivo de chocho (Lupinus mutabilis Sweet) en el barrio Anchilivi, Salcedo, Cotopaxi 2022. - Pullopaxi Taco, Johnnatan David (2022)
In the present research, the evaluation of the effect of the macerate based on dry and tender chocho for the control of pests in the cultivation of chocho (Lupinus mutabilis Sweet) in the Anchilivi neighborhood, Salcedo, Cotopaxi 2022 was determined. A completely randomized block design (DBCA) was used, with a factorial arrangement of (2 * 2) + 2, with 4 replicates per treatment, resulting in 24 experimental units, with a Tukey test at 5%, in an area of 805 m². Two types of chocho macerate were used (tender and dry) with 2 doses (100g and 50g) which were applied at 30, 60, 90 and 120 days in different phenological stages directly to the plant, a chemical control (Cypermethrin 5%) and an absolute control where no product was applied to test the effectiveness of the application of the chocho macerate (dry and tender), the chocho plants to be evaluated were selected at random from within each plot. It was concluded that the best treatment was T5 (chemical control) in the variables at 120 days, height (1.64 cm), number of pods (54.52%), sampling of insects inside the plant (0.23%), sampling of insects outside the plant (0.38%) and sampling of insects on the plant in the soil (0.13%). The second best treatment was T1 (100 g dry chocho) in the variables at 120 days, height (1.56 cm), number of pods (54.52%), insect sampling inside the plant (0.30%), insect sampling outside the plant (0.45%) and insect sampling of the plant in the soil (0.22%). According to the cost benefit of the application of the dried chocho macerate, the best treatment was T1 (100g. dried chocho), which had a value of $ 0.75, which represents that for each dollar invested, $ 0.75 is gained per hectare. To obtain greater effectiveness of the application of the macerate, it is advisable to apply it at the highest doses where the greatest control of insects of the chocho crop was obtained.